Baseball-specific conditioning - Rhea, M. R.; Bunker, D. (International Journal of Sports Physiology and Performance, 2009)
Baseball demands speed, power, and quickness. To perform at a high level, and avoid injuries that are common among baseball players, an evaluation of current trends in strength and conditioning practices is helpful. Based on the demands of the sport and the injury risks, qualified strength and conditioning professionals can develop effective baseball-specific conditioning programs. This commentary briefly covers historical aspects of baseball conditioning, recent injury trends, current practices among elite baseball professionals, and provides suggestions for future improvements in training.